Japanese Characteristics in High-rise Buildings of Tokyo, Japan - Porntavakool, Thanaporrn; Ongsavangchai, Nawit (Journal of Architectural/Planning Research and Studies (JARS), 2020)
This research aims to explain the transition of Japanese characteristics in high-rise buildings using several transferrable procedures, and to verify how much the appearance of Japanese characteristics still remain. A total of 9 selected buildings, which were built after world war II (1960 to 2013), and published in the international data source, were studied. The method included searching the history and the development of high-rise or vertical structures in each period. The data synthesis consisted of studying the 9 buildings across several aspects, such as their physical features, relationship with their surroundings, layout plan, form, interior space, materials in comparison with other buildings, and the origin of the Japanese characteristics. The representative Japanese characteristics, which have been transferred to the present were identified as follows: 1) Human beings and the landscape were considered more important than other features, and this concept was represented only in a symbolic way. 2) Aesthetic from natural processes have changed due to human contrivance. In conclusion, the form and interior space have become modernized and internationalized. 3) The elements were used in the form of adaptation rather than in direct usage in past buildings, however the high-rise buildings still emphasize important Japanese characteristics, which persist to a small extent in every building.